C-Phycocyanin Suppresses Cell Proliferation and Promotes Apoptosis by Regulating the AMPK Pathway in NCL-H292 Non-Small Cell Lung Cancer Cells - Chaowen, H; Dongxuan, H; Dongsheng, H; Jianfeng, P; Fan, Y; Yahui, C; Xiaohua, L (Folia biologica (Praha), 2022)
Non-small cell lung cancer (NSCLC) results in high mortality and has gained increasing attention. C-Phycocyanin (C-PC) has been identified as a potential therapeutic inhibitor for NSCLC, but its underlying mechanism remains obscure. The gene expression of the long noncoding RNA neighbour of BRCAI RNA 2 (NBR2) in NSCLC cells was evaluated by quantitative reverse transcription-PCR. The cell capacity for proliferation and migration was examined by EdU and wound-healing assays. Furthermore, the viability and apoptosis of cells was measured with CCK-8 and annexin V/PI, respectively. Next, the protein level of activation of adenosine monophosphate- activated protein kinase and the rapamycin kinase (mTOR) signalling pathway-associated molecules was evaluated by western blotting. H292 cells were pre-treated with C-PC or transfected with plasmids encoding NBR2 or the shNBR2 plasmid, to over-express or knock down NBR2 expression, respectively. NBR2 expression was robustly down-regulated in NSCLC cell lines compared with a normal cell line (BEAS-2B). NBR2 over-expression inhibited migration and promoted apoptosis of H292 cells. Treatment of H292 cells with C-PC enhanced NBR2 levels in a dose- and time-dependent manner. Downregulation of NBR2 in H292 cells inhibited the activity of C-PC on cell proliferation, viability and clone formation. Further mechanistic investigation showed that the down-regulation of NBR2 abolished the modulatory effects of C-PC on the AMPK/mTOR signalling pathway. In conclusion, C-PC inhibits H292 cell growth by enhancing the NBR2/AMPK signalling pathway.
Keywords: Annexin A5; apoptóza; nemalobuněčný karcinom plic; lidé; Sirolimus; proteinkinasy aktivované AMP; Cell Proliferation; sirolimus; Phycocyanin; Apoptosis; Cell Line, Tumor; Adenosine Monophosphate; nádory plic; Sincalide; AMP-Activated Protein Kinases; Humans; RNA dlouhá nekódující; proliferace buněk; TOR Serine-Threonine Kinases; adenosinmonofosfát; Cell Movement; pohyb buněk; Carcinoma, Non-Small-Cell Lung; fykocyanin; nádorové buněčné linie; RNA, Long Noncoding; annexin A5; sinkalid; TOR serin-threoninkinasy; Lung Neoplasms